(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
GIS Architecture is an essential tool to be placed on comprehending the information of spatial and non spatial data over a space and time. Rural Road Network comprises of group of nodes and links. The Network Configuration is a combination of these links with a directional orientation to the nodes which are the Centre heads of the habitations spread over the space. As most of the features are static in nature there is a need to Geo-Reference permanently and the dynamic interactions in terms of planning, construction, maintenance can be visualized over a time on this spatial frame. To create the rural asset, GIS is a great supportive tool which connects advance technologies and the conventional practices on a common platform. There is a need to decide the type of architecture which matches to the rural asset creation for display, reciprocate interactions, updating, data schema attachment and interfacing with advanced technologies.